94 Guideline development for the management of agitation in the last weeks of life. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Nolan, Kate; Bonwick, Helen; Robinson, Claire; Mills, Mark; Griffiths, A; Shepherd, P; Shah, N
Abstract : Background: Agitation is a distressing and common symptom at the end of life; despite this the evidence for the management of this symptom is poor. Aim: Audit clinical practice around management of terminal agitation with patients and healthcare professionals (HCPs) against regional standards. Use audit outcomes to update regional standards and guidelines Method: Systematic literature review examining the evidence base. Survey of HCPs working in specialist palliative care. Retrospective case note review of patients with a diagnosis of terminal agitation receiving specialist palliative care in hospital, hospice or community settings. Results: Below is a summary from 185 responses from 11 different healthcare settings in the Merseyside area from retrospective case note review: Hospice 54.5%, Hospital 29.7%, Home 11.8%, other including Nursing homes 3%. Main reversible causes documented included: pain; breathlessness: constipation and urinary retention. 94% of patients had medications reviewed. Non–pharmacological interventions formed part of the overall management plan. 82% of patients had psychological and spiritual support offered to the patient and or family. First line pharmacological intervention is Midazolam, Levomepromazine is second line. In 92% of cases a Syringe driver (CSCI) was used. Majority of deaths occurred in 3 days or less Communication with patient and family formed a key theme. At the time of death: Midazolam prescribed in 146 cases (mean 26 mg – range 0–60 mg). Levomepromazine prescribed in 61 cases (Mean 56.8 mg – range 5–250 mg). Haloperidol 25 cases (Mean 3.5 mg – range 1–8 mg). Phenobarbital 9 cases ( Mean 922 mg – range 200–1200 mg). Conclusion: This Audit revealed the challenges and wide variation in practice with regards to management of terminal agitation. These findings have informed an update of the regional palliative care guidelines.